2010
DOI: 10.5194/bg-7-809-2010
|View full text |Cite
|
Sign up to set email alerts
|

The impact of Saharan dust on the particulate export in the water column of the North Western Mediterranean Sea

Abstract: Abstract. Simultaneous measurements of atmospheric deposition and of sinking particles at 200 and 1000 m depth, were performed in the Ligurian Sea (North-Western Mediterranean) between 2003 and 2007, along with phytoplanktonic activity derived from satellite images. Atmospheric deposition of Saharan dust particles was very irregular and confirmed the importance of sporadic high magnitude events over the annual average (11.4 g m −2 yr −1 for the 4 years). The average marine total mass flux was 31 g m −2 yr −1 ,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
132
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 130 publications
(146 citation statements)
references
References 69 publications
13
132
0
1
Order By: Relevance
“…Although little evidence for a direct protective mechanism has emerged from in situ observations (Ingalls et al, 2006;Ploug et al, 2008;, laboratorycontrolled experiments have demonstrated the potential for minerals to inhibit the microbial degradation of OM (Arnarson and Keil, 2005;Engel et al, 2009a;Le Moigne et al, 2013). On the other hand, it has been demonstrated that minerals could increase the velocity at which aggregates sink (e.g., De La Rocha and Passow, 2007;De La Rocha et al, 2008;Thomalla et al, 2008;Engel et al, 2009b; and drive large POC flux events (e.g., Thunell et al, 2007;Lee et al, 2009;Sanders et al, 2010;Ternon et al, 2010). Such fast-sinking POC, negligible within the euphotic zone, is sufficient to explain deep-ocean POC fluxes (Honda and Watanabe, 2010;Riley et al, 2012); this emphasizes the importance of the mode by which carbon is transferred downward when considering carbon flux parameterization.…”
Section: Published By Copernicus Publications On Behalf Of the Europementioning
confidence: 99%
See 2 more Smart Citations
“…Although little evidence for a direct protective mechanism has emerged from in situ observations (Ingalls et al, 2006;Ploug et al, 2008;, laboratorycontrolled experiments have demonstrated the potential for minerals to inhibit the microbial degradation of OM (Arnarson and Keil, 2005;Engel et al, 2009a;Le Moigne et al, 2013). On the other hand, it has been demonstrated that minerals could increase the velocity at which aggregates sink (e.g., De La Rocha and Passow, 2007;De La Rocha et al, 2008;Thomalla et al, 2008;Engel et al, 2009b; and drive large POC flux events (e.g., Thunell et al, 2007;Lee et al, 2009;Sanders et al, 2010;Ternon et al, 2010). Such fast-sinking POC, negligible within the euphotic zone, is sufficient to explain deep-ocean POC fluxes (Honda and Watanabe, 2010;Riley et al, 2012); this emphasizes the importance of the mode by which carbon is transferred downward when considering carbon flux parameterization.…”
Section: Published By Copernicus Publications On Behalf Of the Europementioning
confidence: 99%
“…In light of this fact, an alternative explanation states that correlations between POC and mineral fluxes may result from OM, which acts as "glue" for aggregate minerals that would otherwise not sink Passow and De la Rocha, 2006). Without determining the catalyst for aggregation, Ternon et al (2010) concluded that the simultaneous presence of OM and lithogenic particles is required for the formation of large and fast-sinking particles in the western Mediterranean Sea. Considering the strong spatial and temporal variability of dust-deposition events (Jickells et al, 2005;Mahowald et al, 2009), the water column into which atmospheric particles are deposited is characterized by a wide-ranging OM composition and abundance.…”
Section: Published By Copernicus Publications On Behalf Of the Europementioning
confidence: 99%
See 1 more Smart Citation
“…Another explanation for the missing relationship could be that fine-grained dust accumulates in surface waters until the biological pump produces sufficient organic particles to allow the formation of larger particles which then settle into the deep ocean (Bory et al, 2002;Ternon et al, 2010;Nowald et al, 2015). Cape Blanc dust particles have predominant grain sizes between 10 and 20 µm (Ratmeyer et al, 1999a, b;Friese et al, 2016) and, thus, would sink too slowly to build a deep ocean flux signal.…”
Section: Interaction Between Mineral Dust and The Biological Pumpmentioning
confidence: 99%
“…They are also involved in particle aggregation and act as ballast for sinking organic material (e.g. Armstrong et al, 2002;Ternon et al, 2010), changing the settling velocity of iron adsorbed on particle surfaces. The net effect of dust deposition on DFe in surface waters is therefore influenced by various factors: while the input flux of iron is mainly determined by the Fe solubility and content in dust particles, the loss flux depends on the size and composition of sinking particles, rates of particle aggregation as well as of the Fe adsorption and desorption at particle surfaces.…”
mentioning
confidence: 99%